Peningkatan Keterampilan Berpikir Kritis pada Materi Pecahan Melalui Model Pembelajaran Problem Based Learning (PBL) Siswa Kelas 4 SD N 2 Tahunan - Marsanda Dwi Khanifahi; Anisatuzzahra Anisatuzzahra; Syailin Nichla Choirin Attalina (Jurnal Pendidikan Dirgantara, 2025)
This study aims to improve the critical thinking skills of fourth-grade elementary school students in understanding the concept of fractions through the application of the Problem Based Learning (PBL) model. The background of this study focuses on students' still low abilities in: (1) analyzing mathematical problems; (2) planning solution strategies; (3) drawing logical conclusions when working on fraction problems. This study uses the Classroom Action Research (CAR) design model Kemmis & McTaggart which was implemented at SD Negeri 2 Tahunan during the even semester of the 2024/2025 academic year. The research subjects consisted of 23 fourth-grade students who were selected purposively based on the results of the initial diagnosis. Data collection techniques were carried out by triangulation through: (1) formative evaluation tests; (2) participatory observation sheets; (3) learning video documentation; and (4) field notes. Data were analyzed quantitatively and qualitatively with a comparative descriptive approach. The results showed that the application of the PBL model was proven to be effective in improving: (1) students' critical thinking skills on average from 39.13 (low category) to 92.61 (very good category); (2) classical completeness from 8.7% to 91.3%; and (3) learning activities became more meaningful. Statistical analysis of paired sample t-test showed a significant difference (t=19.09; p<0.05) between before and after treatment. Other important findings include: (1) an increase in students' questioning skills by 78%; (2) an increase in the ability to provide arguments by 82%; (3) an increase in problem-solving skills by 85%. In addition, there was an increase in the following aspects: (1) group cooperation; (2) self-confidence; and (3) active involvement in class discussions.